Alpha lipoic acid attenuates inflammatory response during extracorporeal circulation - Uyar, Ihsan Sami; Onal, Suleyman; Akpinar, M. Besir; Gonen, Ibak; Sahin, Veysel; Uguz, Abdulhadi Cihangir; Burma, Oktay (Clinics Cardive Publ Pty Ltd, 2013)
Aim: Extracorporeal circulation (ECC) of blood during cardiopulmonary surgery has been shown to stimulate various pro-inflammatory molecules such as cytokines and chemokines. The biochemical oxidation/reduction pathways of alpha-lipoic acid suggest that it may have antioxidant properties. Methods: In this study we aimed to evaluate only patients with coronary heart disease and those planned for coronary artery bypass graft operation. Blood samples were obtained from the patients before the operation (PI) and one (P2), four (P3), 24 (P4) and 48 hours (P5) after administration of alpha-lipoic acid (LA). The patients were divided into two groups, control and LA treatment group. Levels of interleukin-6 (IL-6) and -8 (IL-8), complement 3 (C3) and 4 (C4), anti-streptolysin (ASO), C-reactive protein (CRP) and haptoglobin were assessed in the blood samples. Results: Cytokine IL-6 and IL-8 levels were significantly higher after surgery. Compared with the control groups, LA significantly decreased IL-6 and IL-8 levels in a time-dependent manner. CRP levels did not show significant variation in the first three time periods. CRP levels were higher after surgery, especially in the later periods. These results demonstrate that CRP formation depends on cytokine release. C3 and C4 levels were significantly higher after surgery than in the pre-operative period. LA treatment decreased C3 and C4 levels. Therefore, LA administration may be useful for the treatment of diseases and processes where excessive cytokine release could cause oxidative damage. Conclusions: Our findings suggest a possible benefit of using LA during cardiac surgery to reduce cytokine levels.
Keywords: extracorporeal circulation; systemic inflammatory response; oxidative stress; alpha-lipoic acid